PERSEPSI MAHASISWA TENTANG PELAKSANAAN PEMBELAJARAN PADA JURUSAN PENDIDIKAN AGAMA ISLAM FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - Yahdi, Muhammad (Inspiratif Pendidikan, 2019)
The learning process is conducted in an interactive, inspiring, fun, challenging, motivating students to participate actively, giving enough space for the creation of initiative, creativity, and independence, in accordance with the interests of students . In addition, certainly in the learning process, teachers should provide ketauladanan attitude in all academic targets for students . The results of the study describes the results of a very simple descriptive analysis using the percentage formula and formula average. Based on the analysis, the results of this study describe the following matters: ( a) the implementation of the learning process at the Department of the Faculty of Tarbiyah and Teaching PAI UIN Alauddin Makassar, has been going well ( data analysis include: preparation of learning = 3.5; usage schedule and the effective time = 2.9; preliminary activity = 3.4; core activity = 3.2; activities cover = 2.7. ( b ) the results of students' academic learning is also quite good, namely cognitive abilities = 3.3; affective = 3.1; psychomotor = 2.6 ( c ) the supporting factors include: the availability of faculty and professional employees based on their field, the availability of adequate infrastructure, good management of the organization, financing is cheap and affordable, as well as assessment of learning outcomes fair and wise ( the average of the component semuan = 3.7 ) .